Investigation of Chemical Composition of a Steam Turbine Shaft (A Case of Kaduna Refinery) - Garba, D. K.; Muhammad, M. J.; Umar, U. S.; Ozoekwe, N. C. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
An investigation of the chemical properties of Original Equipment Manufacturer’s (OEM) steam turbine shaft and that of locally produced shaft was carried out to determine the chemical composition of the shafts and determine the suitability of the locally produced shaft to replace the OEM turbine shaft that is in constant failure. The chemical analysis carried out on the samples revealed that the OEM turbine shaft is composed of 0.48C, 0.06S, 0.12Ca, 0.99Cr, 0.36Si, 0.71Mn, 0.07P, 0.12Ni, 0.15Cu and 0.39Mo and the locally manufactured steam turbine shaft is composed of 0.38C, 0.07S, 0.038Ca, 0.89Cr, 0.83Si, 0.63Mn, 0.04P, 0.04Ni, 0.16Cu and 0.20Mo. Manganese which was found to increase hardenability and tensile strength is lower in the locally manufactured shaft as compared to the OEM steam turbine shaft. The analysis also showed that carbon, Sulphur, chromium, phosphorus, Nickel and Molybdenum content of the original steam turbine shaft is higher than that of the locally manufactured shaft. The results obtained agree with the ASTM A668 steam turbine shaft requirement under class D standard of the chemical composition.